Analisis Kemampuan Literasi Matematis melalui Model Pembelajaran Berbasis Masalah pada Siswa Sekolah Menengah - Subaryo Subaryo (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2022)
This research is motivated by the low mathematical literacy ability of students. One of the learning models that can develop and facilitate to improve students' mathematical literacy skills is a problem-based learning model, because with a problem-based learning model students are oriented towards real world problems and in the learning stages students report results. work done in groups. The purpose of this study was to determine: analyze the implementation of problem-based learning models for mathematical literacy skills. This study uses a qualitative research approach. The type of research used in this research is library research with the documentation method. Data was collected by collecting literature related to research variables and then classified and analyzed. Based on the results of data analysis, it can be concluded that the implementation of problem-based learning models can improve and have a positive impact on the development of high school students' mathematical literacy skills.